2007
DOI: 10.1186/1471-2458-7-54
|View full text |Cite
|
Sign up to set email alerts
|

Early sexual maturation, central adiposity and subsequent overweight in late adolescence. A four-year follow-up of 1605 adolescent Norwegian boys and girls: the Young HUNT study

Abstract: Background: Early sexual maturation has been associated with overweight that may persist after the completion of biological growth and development. We have prospectively examined the influence of early sexual maturation on subsequent overweight in late adolescence and assessed if this association was modified by central adiposity in early adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
18

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 38 publications
5
61
1
18
Order By: Relevance
“…Several definitions are used to describe timing of puberty: age at menarche (11,12,16,21,(28)(29)(30), age at clinical onset of puberty (12,30,31) and age at peak height velocity (32). Using age at menarche, we found that the development of fat mass is significantly different in girls with an early and a late menarche.…”
Section: Discussionmentioning
confidence: 92%
“…Several definitions are used to describe timing of puberty: age at menarche (11,12,16,21,(28)(29)(30), age at clinical onset of puberty (12,30,31) and age at peak height velocity (32). Using age at menarche, we found that the development of fat mass is significantly different in girls with an early and a late menarche.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, it has been shown that nearly all the influence of early menarche on adult excess weight is a result of the influence of elevated relative weight on early maturation (Freedman et al, 2003;Must et al, 2005). Also, results from a prospective study conducted in Norway showed that early menarche onset was not associated with excess weight in girls that were relatively lean at the entry of the study (Bratberg et al, 2007).…”
Section: Earlier Age Of Menarche Onset and The Risk Of Obesity In Adumentioning
confidence: 99%
“…La presencia de tejido adiposo a corta edad, unida a la maduración sexual temprana (>12,5 años), incrementa el IMC durante la adolescencia (47). En el presente estudio, la diferencia entre grupos en cuanto a la edad de la menarquia no fue significativa.…”
Section: Discussionunclassified